Pengelolaan Keuangan Dalam Menciptakan Sekolah Berdaya Saing di Era 5.0 - Ahmad Tarmizi Hasibuan,; Nurhayani, Nurhayani; Siti Rubiah Dalimunthe,; Mona Hijriah Nasution, (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Previous research has discussed the 4.0 situation in the education sector. There are many old studies that are still relevant today because they aim to improve economic and management theory in creating competitive schools in the 5.0 era. With advances in technology and information, we now realize that schools must be more active and creative to create a learning environment that can keep up with technological advances. This article discusses the financial management process in schools in the 5.0 era which is based on the three pillars of financial management (financial management, education quality, and financial information systems), as well as financial management literature. As a result of this article, the following facts and figures are revealed: 1) Financial Management to improve school quality; 2) Theories about improving the quality/quality of schools; and 3) Demonstration of the use of technology in financial transactions. The data collection method used in this study makes use of a literature review in which the researchers gather information from recent books and journals that may be used as references.